Dwie dekady stosunków Polski z Litwą – wymiar polityczny - Modzelewski, Wojciech Tomasz (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
Lithuania was among the first republics of the disintegrating Soviet Union to announce its declaration of independence, and in September 1991 established diplomatic relations with Poland. In January 1992, both countries signed a joint declaration, and in April 1994 they signed the Treaty on friendly relations and good neighborly cooperation. Over the next 10 years, ways of achieving foreign policy objectives shared by both countries were sought and eventually worked out. Mutual support in pursuit of becoming a member of NATO and of the European Union was visible, which eventually turned into profound relations that were referred to as a strategic partnership. A network of cooperation was formed. It included deep political contacts at all levels and the paying of first foreign visits after being sworn in, which on the Polish side was initiated in 1996 by President A. Kwaśniewski, has become a symbol. Both countries have undertaken joint initiatives to improve energy security and military cooperation, and conduct cross-border and interregional cooperation. The end of the second decade of the two countries’ relations showed, however, that unresolved problems, mainly related to the status of the Polish minority in Lithuania, have been increasingly influencing the policy of steadily building good neighborly relations between Warsaw and Vilnius.